2022
DOI: 10.1093/bib/bbac422
|View full text |Cite|
|
Sign up to set email alerts
|

CReSIL: accurate identification of extrachromosomal circular DNA from long-read sequences

Abstract: Extrachromosomal circular DNA (eccDNA) of chromosomal origin is found in many eukaryotic species and cell types, including cancer, where eccDNAs with oncogenes drive tumorigenesis. Most studies of eccDNA employ short-read sequencing for their identification. However, short-read sequencing cannot resolve the complexity of genomic repeats, which can lead to missing eccDNA products. Long-read sequencing technologies provide an alternative to constructing complete eccDNA maps. We present a software suite, Construc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Subsequently, we analyzed the nanopore sequencing data using the CReSIL 37 tool for further comparison. Results showed that the number of eccDNAs identified by the CReSIL tool was significantly increased (Table S5†).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we analyzed the nanopore sequencing data using the CReSIL 37 tool for further comparison. Results showed that the number of eccDNAs identified by the CReSIL tool was significantly increased (Table S5†).…”
Section: Resultsmentioning
confidence: 99%
“…For a re ned understanding of the eccDNA source mechanisms, analysis pipelines that resolve complex eccDNA composites from multiple break events are necessitated. Applying such advanced technologies, Wanchai and colleagues recently suggested that only 1-2% of the circles in murine cortical tissue comprise a complex, multi-locular genomic origin [102]. Accounting for the suggested capability to embed pathophysiologically impactful sequences, in analogy to the recently described regulator and enhancer functions of long ecDNAs in tumors [47], the modes of interaction with the linear genome will greatly broaden our understanding of small eccDNA in the context of neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Although the method was developed for identification and characterization of plant virus genomes, and includes the ‘annotate’ module that is restricted to viruses annotation, part of the pipeline that outputs eccDNA candidates and their genomic localization can be used for the identification of LTR-RTs. Other long-reads based tools, such as CReCIL ( Wanchai et al., 2022 ) allow not only efficient identification of circular DNA but also annotation and Circos-based visualization of assembled circles, but its performance was tested only on long-reads from mammals eccDNA sequencing. Another tool, ecc_finder ( Zhang et al., 2021 ) is based on a pipeline applied for the analysis of Mobilome-seq data originated from plant tissues ( Lanciano et al., 2017 ).…”
Section: Detection Of Extrachromosomal Circular Dnamentioning
confidence: 99%